Financial Outcomes of the Locus of Control: PLS-SEM Evidence from Croatia - Novokmet Ana Kundid; Vuković Marija (Studies in Business and Economics, 2024)
Raising importance of personality traits within the financial decision-making literature inspired us to conduct a research with locus of control in the main role for achieving financial benefits in personal finance. PLS-SEM analysis was adopted using the data set of 130 Croatian citizens who took part in a questionnaire survey. We confirmed that external locus of control is detrimental to self-control, which afterwards reflects in personal finance management. To be more precise, people with less developed self-control are more prone towards compulsive buying, materialism and indebtedness. Personality traits such as locus of control are usually stable among adults. Thus, mainly self-control can be exercised and improved. That is the key message of this article for external people and various providers of financial literacy programs – change is possible and manageable principally via practicing self-control. Nevertheless, the subsequent studies could offer a more detailed insight into the interplays between locus of control, financial literacy, self-control and financial outcomes.